Optimization of a single-embryo transfer by using time-lapse microscopy in IVF and ICSI programs - N. V. Saraeva; N. V. Spiridonova; M. T. Tugushev; O. V. Shurygina; A. I. Sinitsyna (Медицинский совет, 2020)
Introduction. Due to refinements of assisted reproductive technology, the number of multiple pregnancies has increased substantially. Therefore, transfer of a single embryo, as opposed to multiple embryos, is a top-priority task in ART-based infertility treatment. Time-lapse microscopy (TLM) is a tool for selecting quality embryos for transfer.The aim of the study was to assess the outcomes of single-embryo transfer following embryo incubation in a TLM-equipped incubator in patients undergoing IVF and ICSI.Methods. The study was carried out in 743 infertile women. Single-embryo transfer following incubation in a TLM-equipped incubator was performed in 282 patients, who formed the main group; the control group consisted of 461 patients undergoing singleembryo transfer following a traditional culture and embryo selection procedure. We assessed the quality of transferred embryos, the rates of clinical pregnancy and live birth rates.Results. The groups did not differ in the proportion of IVF and ICSI cycles, terms of age and infertility factors. In the study group, there was a higher proportion of excellent quality embryos for transfer (p = 0.001), a higher proportion of cycles with elective embryo transfer (p = 0.001) and a higher proportion of cycles with cryopreservation of embryos (p <0.001). In the subgroup of non-elective embryo transfer with using of TLM, the clinical pregnancy rate was 10% higher than in the control group (p = 0.03). The live birth rates did not differ between the TLM group and the conventional culture group depending on the type of embryo transfer.Conclusion. Our studies show that the use of time-lapse microscopy can increase the effectiveness of IVF and ICSI programs. Continuous monitoring with short intervals provides more information about the development of embryos than the standard daily assessment.